Ataxia-Telangiectasia with Hyper-IgM Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
A group of eight children with ataxia-tengiectasia (A-T) who presented with serum Ig levels suggestive of hyper-IgM syndrome (HIGM) are reported from the Department of Paediatrics, Reinier de Graaf Gasthuis, Delft, and other centers in the Netherlands, Iceland, and Belgium.